Tobacco use and its relationship to social determinants of health in LGBT populations of a Midwestern State - Pelster, A.; Fisher, Christopher; Irwin, J.; Coleman, J.; Mccarthy, M. (2015)
© Mary Ann Liebert, Inc. 2015. Purpose: Researchers have documented that lesbian, gay, bisexual, and transgender (LGBT) people have a higher proportion of tobacco use as compared to general population smoking rates. This study examined the relationships between tobacco use and social determinants of health in a sample of self-identifying LGBT people who spend time in Nebraska. Methods: A community-based participatory research approach was used to develop an online survey to assess the physical, mental, social, and sexual health of LGBT populations who live, work, or play in Nebraska. Chi-squared and logistic regression analyses explored the use of tobacco among respondents. Results: Of the 770 people who completed the survey, 763 respondents completed questions about smoking status. The prevalence of current smoking among these 763 respondents was 26.47%. Some LGBT-specific social determinants of health had significant relationships to smoking status. However, after controlling for known risk factors of smoking in logistic regression models, these variables were not related to smoking status. Conclusions: This study shows that there is a significant relationship between smoking and several general social determinants of health, including employment status, education, and income as well as binge drinking. Limitations include lack of adequate survey respondents to divide subgroups of LGBT individuals and inherent limitations of convenience sampling, which may not allow for an accurate representation of the situation faced by LGBT in Nebraska. In addition to this, the list of LGBT-specific determinants of health used in the survey may not be exhaustive, and there may be additional factors facing LGBT individuals. Public health professionals can use this information in designing smoking reduction campaigns for LGBT populations in Nebraska and culturally similar regions of the United States. These programs and interventions may want to consider a more holistic approach to smoking cessation grounded in the social-ecological model.